Determinants of firm success: a resource-based analysis - Galbreath, Jeremy Thomas (Curtin University, 2004)
The resource-based view of the firm (RBV) is one the most important areas of research content to emerge in the field of strategic management in the last 15 years. The RBV is prescriptive. That is, the RBV prescribes that competitive advantage stems from those resources that are valuable, rare, inimitable, and nonsubstitutable (VRIN). With rare exception, resources that meet the VRIN criteria are widely purported to be intangible in nature. From a research perspective, the RBV stream tends to be dominated by conceptual discussions and advancements. However, empirical tests of the core premises, or the main prescription, of the theory are argued to be very limited in quantity. To add to the body of empirical research that seeks to verify the main prescription of the RBV, this research undertakes a new and different level of analysis, one that has not been previously tested. Given that firms compete with both tangible and intangible resources, the present study is interested in determining if, as the RBV implicitly prescribes, resources that are intangible in nature are more important determinants of firm success than tangible resources. Although the research question is basic and fundamental, it has rarely been appropriately or adequately tested within the RBV stream, as is demonstrated by this thesis. To carry out the research, this study offers a conceptual model of the firm’s resource pool that includes tangible assets (financial and physical assets), intangible assets (intellectual property assets, organizational assets, reputational assets), and capabilities. A series of hypotheses are posited to explore the proposition that intangible resources contribute more greatly to firm success, on the dimensions of sales turnover, market share, and profitability, than tangible resources.A field survey, administered to 2000 manufacturing and services businesses operating in Australia, is used to gather the data. Of the 2000 surveys sent, the hypotheses are empirically tested using multiple hierarchical regression analysis on a final sample of 291 firms. Control variables include firm age and Porter’s five forces of industry structure. Based on the results, verification of the RBV’s main prescription can not be supported unequivocally. Intellectual property assets, for example, do not have a statistically significant association with firm success, after accounting for the effects of tangible resources and the control variables. Organizational assets, however, not only explain additionally significant variation in firm success, after accounting for the effects of tangible resources and the control variables, but make among the greatest, unique contribution to firm success based on the size of the beta coefficients. Reputational assets offer additional explanatory power to predicting firm success after accounting for the effects of tangible assets and the control variables, but only with respect to one measure of firm success does its beta coefficient make a larger, unique contribution than financial assets. Lastly, contrary to theory, capabilities are not the single most important determinant of firm success, after accounting for the effects of intangible assets, and tangible and intangible assets, in two separate hierarchical regression equations. This finding is surprising and explanations are provided. Overall, the study raises some questions with respect to just which resources are the most important determinants of a firm’s market and financial success and offers a fruitful avenue for further research.